(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Career development planning is a critical element of succession planning, focusing on systematically preparing employees for future organizational roles. Career Development planning face significant challenges such as Inconsistent and inadequate implementation of career development practices particularly unequal access to training, mentorship and promotion opportunities which continue to undermine employee performance in public health facilities in Bungoma County. Thus the primary aim of the research was to establish the effect of Career Development Planning on Health Sector performance in the County Government of Bungoma, Kenya. The research was guided by the Human Capital Theory and was conducted in the among the Health Sector in the County Government of Bungoma. This research employed a descriptive survey research design, analysing data through descriptive statistics, including mean, standard deviation, frequency, and percentage, as well as inferential statistics, comprising Pearson correlation and regression analysis, given in tabular form the target population of 240 respondents was drawn from the County Referral Hospital and 9 Sub-County Hospitals. Simple random sampling was used to select 15 Heads of Ward Sections while census method was adopted in selecting 94 respondents within the County Ministry of Health to give a total of 109 respondents as the sample size. The research incorporated primary data sources collected using closed and open-ended questionnaires and interviews, which were pretested in Turkana County to evaluate validity and reliability. Quantitative data collected through questionnaires were analysed using SPSS, while qualitative data from open-ended questions and interviews were subjected to thematic analysis. The findings indicated that all aspects of Career Development Planning exhibited a positive and significant correlation with Health Sector Performance in Bungoma County, Kenya. The results indicated that Health Sector Performance increases by 0.321 units for each unit rise in Career Development Planning (β2=0.321, p<0.05). This outcome suggests that the County Government of Bungoma should develop and implement a Career Development plan as to improve on the performance of the health sector.